Inequality and Optimal Redistributive Tax and Transfer Policies - Zee, Howell (IMF Working Papers; Working Paper ;, 1999)
This paper explores the revenue-raising aspect of progressive taxation and derives, on the basis of a simple model, the optimal degree of tax progressivity where the tax revenue is used exclusively to finance (perfectly) targeted transfers to the poor. The paper shows that not only would it be optimal to finance the targeted transfers with progressive taxation, but that the optimal progressivity increases unambiguously with growing income inequality. This conclusion holds up under different assumptions about the efficiency cost of taxation and society's aversion to inequality.